Nem katolikus diákok a királyi jogakadémiákon 1777 és 1850 között - Juhász, Réka (Gerundium, 2017)
Not catholic Students at Royal Law Academies between 1777 and 1850. In the following study my goal is to examine an unusual question about the royal academies: the religious structure of the students. The most students were catholic in this institutions. The explanation of this fact is these academies were founded by Maria Theresia, and before that were owned by the Jesuit order. From 1777 these academies were state institutions. However, the Protestants had their own school network in this period, we could also find not catholic students at the register books. I would like to examine these students’ social background, and try to answer the question, why they chose for the royal academies. All of these data are collected by the MTAELTE Histories of Universities Research Group.